2010
DOI: 10.1577/m09-199.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drought Conditions on Brown Trout Biomass and Size Structure in the Black Hills, South Dakota

Abstract: We evaluated the influence of drought conditions on the biomass of brown trout Salmo trutta in Spearfish Creek, upper Rapid Creek, and lower Rapid Creek in the Black Hills of western South Dakota. Stream discharge, mean summer water temperature, the biomass of juvenile and adult brown trout, and brown trout size structure were compared between two time periods: early (2000)(2001)(2002) and late drought (2005)(2006)(2007). Mean summer water temperatures were similar between the early-and late-drought periods in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…In a previous study on Brown Trout populations in Black Hills streams, James et al (2010a) found that biomass of Brown Trout declined significantly in Spearfish Creek following a drought. In Rapid Creek, biomass of large Brown Trout also declined following the drought; however, mean biomass of small Brown Trout increased appreciably from 14 to 73 kg/ha (James et al 2010a). The increase in small Brown Trout biomass was coincident with the occurrence of D. geminata blooms in Rapid Creek, and since then has remained relatively high (James et al 2010a).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…In a previous study on Brown Trout populations in Black Hills streams, James et al (2010a) found that biomass of Brown Trout declined significantly in Spearfish Creek following a drought. In Rapid Creek, biomass of large Brown Trout also declined following the drought; however, mean biomass of small Brown Trout increased appreciably from 14 to 73 kg/ha (James et al 2010a). The increase in small Brown Trout biomass was coincident with the occurrence of D. geminata blooms in Rapid Creek, and since then has remained relatively high (James et al 2010a).…”
Section: Discussionmentioning
confidence: 89%
“…The selected sampling reaches from Castle and Spearfish creeks have not experienced D. geminata blooms. In addition, the three sampling reaches were chosen because they have been previously researched (James et al 2010a(James et al , 2010b and because these locations have historical composition and abundance data for salmonids (Bucholz and Wilhite 2009). Each of these sampling reaches was surveyed for D. geminata coverage, Brown Trout diet and body condition, and invertebrate composition and abundance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations